Erythrocytosis in congenital heart defects: hints for diagnosis and therapy from a clinical case - Borsani, Oscar; Varettoni, Marzia; Riccaboni, Giacomo; Rumi, Elisa (Frontiers in Medicine, 2024)
Erythrocytosis is one of the most common abnormalities that clinical hematologists, general practitioners, and internal medicine specialists could have to face off in their routine clinical practice. While diagnostic criteria for primary erythrocytosis (i.e. polycythemia vera) are well known and characterized, there are several causes of secondary erythrocytosis that should be kept in mind to avoid misdiagnosis.Congenital heart defects are rarely cause of secondary erythrocytosis as they are normally recognized and treated at an early stage.Eisenmenger syndrome is a complex clinical syndrome that arise as consequence of an untreated congenital heart defect associated with large intracardiac shunt. The clinical picture of this syndrome usually includes a severe erythrocytosis that could tempt clinicians to start an intensive phlebotomy (or venesection) program. However, clinicians should be aware that erythrocytosis in Eisenmenger syndrome is a compensatory mechanism aimed at improving blood oxygen-carrying capacity; accordingly, phlebotomies should be reserved for those cases complaining hyperviscosity symptoms.Here we present a case of an adult female patient with Eisenmenger syndrome that has been evaluated because of severe and persistent erythrocytosis. In this case we present a step-by-step approach by which clinical hematologist could proceed to reach the definitive diagnosis. We'll also provide some hints that could help clinicians when choosing the best treatment strategy to avoid unnecessary and potentially harmful procedures.